A New Dynamical System to Study the Spread of SARS -COV 2 based on Data from Greece - Vachtsevanos, Vasileios; Meletlidou, Efthymia (Discontinuity, Nonlinearity, and Complexity, 2026)
The COVID-19 pandemic has troubled both medicinal and scientific personnel for more than two years. This epidemic has proven resilient to medical and social measures undertaken worldwide. Modeling a pandemic of this size is an arduous task, partly because of the virus’ mutability and partly due to the diverse and complex ways that each government is trying to reduce the effects of the pandemic, by using different measures with a varying degree of success. In this work, we will try to design an adaptable dynamical system, which can be adjusted to make predictions for different populations and different measures to fight the pandemic. Additionally, we will present a novel idea for examining whether an epidemiological system, i.e., the epidemic will end or not in-dependently of the system’s internal characteristics.